Time Course of Recovery after Cycling Repeated Sprints - Milioni, Fabio [UNESP] (2021)
Purpose The present study investigated the recovery of performance and neuromuscular fatigue after cycling repeated sprints. Methods Ten participants performed two sessions of repeated sprints (one session: 10 × 10-s sprints, 30-s recovery) separated by 24 h (R24-S1 and R24-S2) and two sessions separated by 48 h (R48-S1 and R48-S2). The recovery condition (i.e., 24 or 48 h) was randomized and separated by 1 wk. All sessions were performed on a recumbent bike, allowing minimal delay between sprints termination and neuromuscular measurements. Neuromuscular function of knee extensors (neuromuscular assessment [NMA]) was assessed before sessions (presession), after the fifth sprint (midsession), and immediately after (postsession). Before sessions, baseline NMA was also carried out on an isometric chair. The NMA (bike and chair) was composed of maximal voluntary contraction (MVC) of knee extension and peripheral neuromuscular stimulation during the MVC and on relaxed muscle. Results The sprints performance was not significantly different between sessions and did not presented significant interaction between recovery conditions. MVC was significantly lower at R24-S2 compared with R24-S1 (-6.5% ± 8.8%, P = 0.038) and R48-S2 (-5.6% ± 8.2%, P = 0.048), whereas resting potentiated high-frequency doublet (Db100) was lower at R24-S2 compared with R24-S1 (-10.4 ± 8.3, P = 0.01) (NMA on chair). There were significant reductions in MVC (>30%, P < 0.001) and Db100 (>38%, P < 0.001) from pre- to postsession in all sessions, without significant interactions between recovery conditions (NMA on bike). Conclusion Cycling repeated sprints induce significant fatigue, particularly at the peripheral level, which is fully restored after 48 h, but not 24 h, of recovery. One versus two days of recovery does not affect neuromuscular fatigue appearance during cycling repeated-sprint sessions.